Strengths and Weaknesses of the Romanian Health System Management - Ion POPA; Simona Cătălina ȘTEFAN; Adriana GIURGIU; Mircea Stelian DRĂGHICI (Transylvanian Review of Administrative Sciences, 2016)
The purpose of this paper is to highlight the main strengths and weaknesses of health services management in Romania and the manner in which the key stakeholders relate to them. Taking into consideration that those who can provide the most valuable information are those directly involved, the identifi cation of strengths and weaknesses is based on an empirical research carried out from a dual perspective: that of the employees and specialists from the healthcare system and that of the patients, as their benefi ciaries. The collected data were also used for testing the research hypotheses and most of them were validated. In the end, we point out a series of directions in order to improve the performance and effectiveness of the Romanian health system management.